The labour market intentions and behaviour of stay-at-home mothers in Western and Eastern Europe. (December 2016) - Gauthier, Anne H.; Emery, Tom; Bartova, Alzbeta
Abstract: Despite recent increases in female labour force participation across Europe, a non-negligible proportion of women continue to remain out of the labour force for short or longer periods of time. Among the six countries included in this paper, stay-at-home mothers represent on average 33% of all mothers with children under the age of 12. Using two waves of data from the Generations and Gender Survey, we examine cross-national differences in the labour market intentions and behaviour of stay-at-home mothers. In particular, we ask the questions of what individual- and societal-level factors influence stay-at-home mothers' intention to join the labour force, and what factors allow (or prevent) them from realizing their intentions. The results reveal that traditional personal attitudes towards working mothers deter stay-at-home mothers from intending to join the labour force. Moreover, such traditional personal attitudes, combined with financial security, further boost mothers' realization of negative work intention (i.e. the intention to stay at home). We also found some evidence of the role of societal context but only in the realization of negative intention.